GAMBARAN GLUKOSA DARAH DAN KOLESTEROL PADA PEDAGANG DI OBYEK WISATA SANGEH KECAMATAN ABIANSEMAL KABUPATEN BADUNG - ida arjani (Meditory : The Journal of Medical Laboratory, 2017)
Bacground The level of glucose in the blood must be kept in a sufficient concentration to provide nutrition for body organs. But on the contrary, the concentration of glucose that is too high can have a negative impact as osmotic diuresis and cellsdehydration. Therefore, blood glucose should be maintained in a constant concentration. Objective The purpose of this study is to describe the levels of blood glucose and cholesterol in traders at Sangeh tourist attraction, Abiansema, District of Badung. Methods This study is a descriptive study. Population of this research was all traders at Sangeh Tourist attraction or about 132 traders. 50 sample was selected by random sampling. Results showed blood glucose levels at any of the 50 samples, 84% normal and 16% higher. Blood glucose levels> 140 mg / dL by age group most in the age range 55 years and over is 12%, the blood glucose levels 140 mg / dL by gender be obtained at most in the female sex is as much as 10%. Test results cholesterol levels of 50 samples of 24% normal and 76% high cholesterol levels> 200 mg / dL based on age in range 55 years and over 36% whereas cholesterol levels 200 mg / dL highs also in the female sex is as much as 60%. Keywords : Blood glucose, cholesterol, traders